The effects of teleworking on the mental health of public servants: A scoping review - Péricles Nóbrega; Diva Ester Okazaki Rowe (Contextus, 2025)
Background: The widespread adoption of teleworking by the brazilian public administration could have implications for mental health, especially in the face of the Covid-19 pandemic. The literature points to both negative and positive impacts of the implementation of this way of working, so that, especially in the public service, its relationship with health processes remains poorly demarcated and poorly defined.